Family Support in Self-Management at Home: a Descriptive Study among Children with Cancer - Febrina, Cory; Kartika, Imelda Rahmayunia; Rezkiki, Fitrianola; Mariyana, Rina (Universitas Fort De Kock Bukittinggi, 2025)
Background: Cancer is still a significant health problem today. In 2020, an estimated 19.3 million new cancer cases and nearly 10 million cancer deaths occurred worldwide. Cancer patients and their families need support to manage them effectively, emotionally and lifestyle. This study aims to see a picture of family support for clients with cancer. Methods: This research uses a quantititatif researce Home in Padang City, in mid-August 2024. The sample for this study was 26 who filled out the questionnaire, describing the characteristics of the respondents.Results: The most significant data with the highest category value can be seen in the first statement which represents the indicator of emotional support. The instrument used